ESTIMASI KANDUNGAN SERPIH (Vsh), POROSITAS EFEKTIF (∅e) DAN SATURASI AIR (Sw) UNTUK MENGHITUNG CADANGAN HIDROKARBON PADA RESERVOAR LIMESTONE LAPANGAN “PRB” DI SUMATERA SELATAN MENGGUNAKAN DATA LOG DAN PETROFISIKA - Leo Rivandi Purba; Bagus Sapto Mulyatno (Engineering Faculty Universitas Lampung, 2018)
Log and petrophysics data of research area are that located in South Sumatera Basin, exactly at formation Baturaja will be used for counting the hydrocarbon stock in research field. There are 3 the well datas prosessed to determine the prospect layer of hydrocarbon and estimate the hydrocarbon stock in the productive zone by using 1 petrophysic data from well PRB-3. In order to determine the productive zone of hydrocarbon, the first thing to do is to determine the petrophysics parameters. Parameters used is shale content, effective porosity and water saturation. The value of shale content on “PRB” field shows that reservoir is clean from shale minerals. But, based on the saturation of water, type hydrocarbon in reservoir it is natural gas. Based value of three parameters last, the field “PRB” having 6 zone productive hydrocarbon in each ecploratory wells. Then, determine zone net pay that had been determined by using the cut-off of shale content which is 8% it means hydrocarbon will be produced if the value of shale content under 8%, effective porosity is 5% it means hydrocarbon will be produced if the value of porosity of effective larger than 5% and water saturation is 70% it means that the value of water saturation on field “PRB” must be less than 70% that hydrocarbon can be produced. Average thickness of the net pay in well PRB-1 is 6.78 meter. In well PRB-2, the average thickness is 7.37 meter while in well PRB-3 it is 3,825 meter. The average thickness from those three wells is 3,005 meter. The mean effective porosity of those 3 wells is 8,1% and the mean water saturation is 27,2%. Gas volume formation factor (Bg) is 0,0226 bbl/SCF which the area width is 28 km2. Natural gas stock (OGIP) in this research area is 7,764 BSCF.